2018
DOI: 10.3389/fcimb.2018.00285
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of the Cas9 Gene in Virulence of Campylobacter jejuni

Abstract: Campylobacter jejuni is considered as the leading cause of gastroenteritis all over the world. This bacterium has the CRISPR–cas9 system, which is used as a gene editing technique in different organisms. However, its role in bacterial virulence has just been discovered; that discovery, however, is just the tip of the iceberg. The purpose of this study is to find out the relationship between cas9 and virulence both phenotypically and genotypically in C. jejuni NCTC11168. Understanding both aspects of this relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
1
24
0
1
Order By: Relevance
“…These results suggest that the cas3 gene may participate in the regulation of bacterial biofilm formation. A study in C. jejuni, containing a type II-C CRISPR-Cas system, also supports our findings that the C. jejuni WT strain has a stronger capability to form biofilms than mutant strains [66]. This showed that CRISPR-Cas systems play a role in biofilm formation to alter virulence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that the cas3 gene may participate in the regulation of bacterial biofilm formation. A study in C. jejuni, containing a type II-C CRISPR-Cas system, also supports our findings that the C. jejuni WT strain has a stronger capability to form biofilms than mutant strains [66]. This showed that CRISPR-Cas systems play a role in biofilm formation to alter virulence.…”
Section: Discussionsupporting
confidence: 88%
“…Cells grown to a cell density of~2 × 10 5 cells/well in 24-well cell culture plates (Corning Cell-Bind) were infected with Salmonella strains at multiplicities of infection (MOI) of 100:1 bacteria:cell ratio. Invasion and intracellular survivability were accessed by the colony-forming units (CFU) count assay as previously described [66]. For MH-S, RAW264.7, SW480, SW620, and IPEC-J2 cells, the bacterial numbers of internalization were assessed at the post-infection time points indicated in the figures, respectively.…”
Section: Cell Culture Infection Assaysmentioning
confidence: 99%
“…GBS contains a type II CRISPR/Cas locus, which includes the endonuclease effector Cas9 and additional CRISPR-associated genes: cas1, cas2 , and csn2 (involved in spacer acquisition during CRISPR interference) (Figure 1A; Nunez et al, 2014). Based on recent studies (Sampson et al, 2013; Dugar et al, 2018; Shabbir et al, 2018), we hypothesized that this system would contribute to GBS pathogenesis. To investigate the role of Cas9 specifically, we generated Δ cas9 mutants in ST-17 strains by precise allelic-exchange mutagenesis as described previously (Jeng et al, 2003) and in the section “Materials and Methods.” One Δ cas9 mutant was created in the strain COH1, a widely used GBS clinical isolate derived from a case of neonatal invasive disease (Kuypers et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Group A Streptococcus Cas9-mediated control of key virulence determinats finds a parallel in Cas9-mediated regulation of BLP in F. novicida , which enables the pathogen to dampen TLR2-dependent inflammatory response and to survive within host cells (Sampson et al, 2013). Also, the observed broad effect of Cas9 on GAS virulence regulation is reminiscent of the multiple virulence pathways regulated by the CRISPR-Cas9 system of C. jejuni , including those encoding lipoproteins, flagella, and chemotaxis-related factors (Shabbir et al, 2018).…”
Section: Discussionmentioning
confidence: 99%